On the causal relationship between trade-openness and government-size: Evidence from OECD countries - Molana, H; Montagna, C; Violato, M (2011)
The compensation hypothesis predicts a positive causation from international economic openness to the size of the public sector, as governments step in to perform a risk mitigating role to counterbalance the increasing exposure to external risk and the economic dislocations caused by growing international openness. We use time series data from 22 OECD countries over the period 1955-2003 and examine the statistical significance of both long-run and short-run causality channels in each country separately. Our findings fail to provide an overwhelming support for this hypothesis, with only five countries showing some evidence in its favour. Copyright © 2011 Inderscience Enterprises Ltd.